Epidemiology of Orthopaedic Admissions at A Teaching Hospital of Eastern Nepal - Mishra, Bibhuti Nath; Jha, Anuja; Gupta, Yogendra (Journal of Nobel Medical College, 2017)
Background: There are many other reasons besides fracture for which a patient could potentially be admitted to orthopaedic inpatient care. The goal of this retrospective review was to analyze the spectrum of orthopaedic admissions to a tertiary level teaching hospital of Nepal. Material & Methods: This retrospective descriptive epidemiological study was based on patients admitted for orthopaedic inpatient care at a tertiary level health care center of eastern Nepal. Registry data of 1 year was used to analyze the spectrum of orthopaedic admissions. Results: Male admission outnumbered females with a ratio of 1.82:1. Trauma accounted to majority of Orthopaedic admissions (67.9%) and Infection lied second in order (12.4%). Upper and Lower limb fractures (with right sided dominance) contributed to highest numbers of trauma respectively. Incidence of closed to open fracture was 5.45:1. More than half of trauma and fractures involved the 10 – 39 years age group with predominance in 10-19 years. Fracture incidence was higher among men than women until 59 years of age after which the gender ratio reversed. Conclusions: Leading cause for orthopaedic admission was Trauma accounting more than 2/3 of the total. Biasness in gender admission reflects true picture of male dominated society. Upper limb injury, right side and closed fractures were dominating. Sexual dimorphism was apparent in fractures which may be due to higher rates of Osteoporotic fractures in elderly females. Journal of Nobel Medical College Volume 6, Number 1, Issue 10 (January-June, 2017), Page: 56-62